Pediatric Deep Brain Stimulation for Therapy and Neuroenhancement: Ethical, Clinical and Legal Dimensions - Minagia, Melpomeni (Bioethica, 2025)
Deep Brain Stimulation (DBS) is traditionally applied in adults for the therapy of certain neurological and psychiatric disorders. Except for adults, it can also be implemented in children, but its applications in pediatrics are limited. A groundbreaking scenario regarding the future of DBS is its potential use beyond the restoration of human health, in the field of neuroenhancement. However, the new applications of DBS present serious ethical, clinical, and legal concerns, which are examined in this paper. In the beginning, the applications of pediatric DBS are presented, along with the method’s potential short- and long-term effects. Subsequently, the concept of “neuroenhancement”, contrasted with “therapy”, and the potential role of pediatric DBS in this domain are analyzed. Moving on to the ethical considerations of pediatric DBS, a wide range of topics are covered, involving safety issues, authenticity, decision-making, and social concerns. In the section on clinical dimensions, the importance of conducting relevant clinical trials as well as their challenges are elucidated. Afterward, as the legal framework of DBS devices is examined, regulations both for medical and non-medical devices are provided, depending on the specific DBS application. These discussions serve as a preparation for the proposal of recommendations, from an ethical, clinical, and legal perspective. The overall purpose of this paper is to provide pathways for the alignment of scientific advancement with the welfare of children.